(3ajV GdbOjQ TQM GdLGeY GdUZjQs - (3GdMOGOj GdbGgQj GdefGhj, Rjf GdOjf, eMeO YHO GdQADa Hf JGL GdYGQajf Hf Ydj Hf Rjf GdYGHOjf, J (B1031 (3g`s ((3Ndjds)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPjYd GdEfSGf gh GdLGeY GdUZjQ hHYO(B) (3agPG eG GTJOJ Edjg MGLI GdeJage Hd hcd eOQS heYde ef TQM Ydi GdLGeY GdUZjQ ddMGaX GdcHjQ GdEeGe GdLdGd GdTgjQ (B( (3jYfj GdSjhWj (B)s
(3BNQgG (B:s
(3abGd dg QLd SeYJ gPG ef YeQ abGd ef NjQ ef YeQ ef QShd Gddg Udi Gddg Ydjg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 204s
(3eYLe GdeDdajf (B2 / 143s
(3cTa GdXfhf (B1 / 561s
(3GdHOQ GdWGdY (B1/ 357s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs